DNA methyltransferase 3b regulates articular cartilage homeostasis by altering metabolism - Jie Shen; Cuicui Wang; Daofeng Li; Taotao Xu; Jason Myers; John M. Ashton; Ting Wang; Michael J. Zuscik; Audrey McAlinden; Regis J. O’Keefe (JCI Insight, 2017)
Osteoarthritis (OA) is the most common form of arthritis worldwide. It is a complex disease affecting the whole joint but is generally characterized by progressive degradation of articular cartilage. Recent genome-wide association screens have implicated distinct DNA methylation signatures in OA patients. We show that the de novo DNA methyltransferase (Dnmt) 3b, but not Dnmt3a, is present in healthy murine and human articular chondrocytes and its expression decreases in OA mouse models and in chondrocytes from human OA patients. Targeted deletion of Dnmt3b in murine articular chondrocytes results in an early-onset and progressive postnatal OA-like pathology. RNA-Seq and methylC-Seq analyses of Dnmt3b loss-of-function chondrocytes show that cellular metabolic processes are affected. Specifically, TCA metabolites and mitochondrial respiration are elevated. Importantly, a chondroprotective effect was found following Dnmt3b gain of function in murine articular chondrocytes in vitro and in vivo. This study shows that Dnmt3b plays a significant role in regulating postnatal articular cartilage homeostasis. Cellular pathways regulated by Dnmt3b in chondrocytes may provide novel targets for therapeutic approaches to treat OA.